Gene expression of a canopy‐forming kelp, Eisenia bicyclis (Laminariales, Phaeophyceae), under high temperature stress. Issue 4 (13th July 2022) - Hara, Yoshino; Otake, Yui; Akita, Shingo; Yamazaki, Tomokazu; Takahashi, Fumio; Yoshikawa, Shinya; Shimada, Satoshi
SUMMARY: To understand the high temperature stress acclimation of a canopy‐forming kelp, RNA‐seq analysis was performed on cultured Eisenia bicyclis (Kjellman) Setchell (Laminariales, Phaeophyceae), a major component species of kelp forests along the coast of Japan. We established a culture strain from a population at the northernmost distribution limit of this species and measured photosystem II activity in young sporophytes. We found that photosystem II activity was lower at 25°C than at 5–15°C, thus, comparative RNA‐seq analysis was conducted between cultivated young thalli of E. bicyclis at 15°C and 25°C. Comparison with the expression genes revealed 277 up‐regulated genes and 327 down‐regulated genes at 25°C. The most up‐regulated gene was 3‐ketoacyl‐CoA thiolase, which is related to fatty acid degradation. This enzyme has been reported to positively regulate abscisic acid (ABA) signaling in Arabidopsis thaliana (Brassicaceae). In addition, heat shock proteins, ATP synthase, NADH‐dehydrogenase, and L‐ascorbate peroxidase were up‐regulated. The most down‐regulated gene was taurine catabolism dioxygenase TauD/TfdA. Genes related to fatty acid metabolism, photosynthesis, and synthesis of cell wall components were down‐regulated. These results suggest that E. bicyclis may counteract high temperature stress by up‐regulating genes involved in protein stabilization, energy production and antioxidant processes. Conversely, photosynthesis and other metabolic processes may be damaged due to the inability to withstand high temperature stress.